2010
DOI: 10.3892/or_00000884
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Galectin-1 as a novel biomarker in nasopharyngeal carcinoma by proteomic analysis

Abstract: Abstract. Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumors in southern China and Southeast Asia. It is characterized as a multistep process involved in multiple genetic and epigenetic events. The mechanism of carcinogenesis still needs to be further clarified. In this study, two-dimensional gel electrophoresis, matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF-MS), RT-PCR, Western blot and immunohistochemical (IHC) analyses were used to detect Gale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Evidence from a variety of cancer types suggests that the expression of galectin-1 is frequently higher in tumor tissues in contrast with healthy or benign tissues. Malignancies of the reproductive organs, gastrointestinal tract, lymphatic malignancies, myeloproliferative tumors, respiratory and urinary system, thyroid, and skin tumors all exhibit this pattern [ 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Although three studies found that galectin-1 expression was decreased in head and neck squamous cell carcinoma, cancers of the uterus, and prostate cancer, these results do not agree with those of the majority of studies, which may indicate that patient demographics, tumor subtypes, or methodologies may differ [ 241 , 242 , 243 ].…”
Section: Types Of Cancer Biomarkersmentioning
confidence: 99%
“…Evidence from a variety of cancer types suggests that the expression of galectin-1 is frequently higher in tumor tissues in contrast with healthy or benign tissues. Malignancies of the reproductive organs, gastrointestinal tract, lymphatic malignancies, myeloproliferative tumors, respiratory and urinary system, thyroid, and skin tumors all exhibit this pattern [ 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Although three studies found that galectin-1 expression was decreased in head and neck squamous cell carcinoma, cancers of the uterus, and prostate cancer, these results do not agree with those of the majority of studies, which may indicate that patient demographics, tumor subtypes, or methodologies may differ [ 241 , 242 , 243 ].…”
Section: Types Of Cancer Biomarkersmentioning
confidence: 99%
“…At present, CEA is a recurrence-related biomarker for colorectal tumors. 3 Some studies reported early predictive biomarkers for NPC, such as HSP27, 4 cathepsin D and keratin 8, 5 AMG and CFB, 6 Galectin-1, 7 SAA, 8,9 and EBV DNA. However, these biomarkers still lack a high predictive value in the clinic.…”
Section: Introductionmentioning
confidence: 99%